INTERRELATIONS OF SERVICE BEHAVIOUR AND SEMINAL ATTRIBUTES OF HAMPSHIRE BOARS - CHUTIA, T; TAMULI, MK; BISWAS, RK; DEKA, BC; SINHA, S; GOSWAMI, J (The Indian Journal of Animal Reproduction, 2022)
Forty ejaculates form five Hampshire boars (8 from each) were collected by simple fist method using a dummy. The service behaviour in terms of reaction time was positively correlated (p<0.05) with strained volume and total ejaculate volume (r=0.314 and 0.326, respectively). The service behaviour in terms of ejaculation time was positively correlated (p<0.05) with gel mass volume, strained volume, total ejaculate volume and total sperm output (r=0.722, 0.816, 0.805 and 0.335, respectively), and was negatively correlated (p<0.05) with sperm concentration (r=-0.533). The gel mass volume was positively correlated (p<0.05) with strained volume and total ejaculate volume (r=0.861 and 0.820, respectively). Also, between the latter two parameters existed a positive correlation (r=0.944, p<0.05). The gel mass volume, strained volume and total ejaculate volume was positively correlated (p<0.05) with total sperm output (r=0.327, 0.326 and 0.494, respectively), and was negatively correlated (p<0.05) with sperm concentration (r=-0.561, -0.690 and -0.572, respectively). The gel mass volume was positively correlated (p<0.05) with live spermatozoa (r=0.321). In brief, service behaviour (reaction time and ejaculation time) and gel mass volume had significant correlations with seminal attributes, thus, these parameters can be the components of breeding soundness assessment in Hampshire boars.